Analysis Potential of Dadih as a Treatment for Diabetes Mellitus Based on Histopathological Images of the Pancreas in Mice (Mus musculus) - Marlin Brigita L.; Hadits Lissentiya Armal; A. Zakaria Amien (Fakultas Ilmu Kesehatan, 2023)
The pathogenesis of Diabetes Mellitus is complex with one of the basic factors causing the disease is oxidative stress. Foods containing probiotics are reported to suppress oxidative stress. Probiotics containing L.acidophillus and L.casei are known to reduce oxidative stress and are antidiabetic. This happens because casei can reduce oxidative stress and suppress CD4 cells effectively, accompanied by a reduction of pro-inflammatory molecules so that it has an antioxidant effect but can also modulate the immune system. To see the role of dadih in this study, the research will be conducted using mice which are divided into three groups, namely the negative control group, the positive control group and the treatment group randomly. Blood sampling aims tomeasure blood glucose levels of mice using a glucometer. Histological observation of the mice's pancreatic organs was carried out to determine theantidiabetic effect of curd. The results of the One-Way ANOVA test showed that there was a significant difference in each treatment group (p=0.000). Giving curd can improve the pancreas of mice with diabetes mellitus seen from the histopathological picture that has pyknosis. The pathogenesis of Diabetes Mellitus is complex with one of the basic factors causing the disease is oxidative stress. Foods containing probiotics are reported